(3GdXQGFa hGddWGFas - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3jhSa Hf fYeGf s)
(3ChdgG (B:s
(3MeOkG MeOkG dNGdb GdNdb HGSW GdQRb hcGO jMci hUhH GdeRf efScH dh cGf Wdb GdeMjG s
(3BNQgG (B:s
(3hbGd BNQ GdZhK ef TgQ GdUjGe bO UGQ di eKd GddLGe Cf CeJY HGdWYGe hGfOGeI hGdeOGe Je s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs